2017
DOI: 10.3390/ijms18092005
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of the PHD-Finger Family Genes and Their Responses to Environmental Stresses in Oryza sativa L.

Abstract: The PHD-finger family has been demonstrated to be involved in regulating plant growth and development. However, little information is given for its role in environmental stress responses. Here, we identified a total of 59 PHD family genes in the rice genome. These OsPHDs genes were located on eleven chromosomes and synteny analysis only revealed nine duplicated pairs within the rice PHD family. Phylogenetic analysis of all OsPHDs and PHDs from other species revealed that they could be grouped into two major cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 62 publications
1
28
0
Order By: Relevance
“…8). This means that some PHD finger genes may play important roles in plant adaption to adverse environmental stresses, an idea that was also supported by other studies [61, 6466]. These identified PHD finger genes can then serve as a source of candidate genes for genetic engineering and improvement of Brassica crops against abiotic stresses.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…8). This means that some PHD finger genes may play important roles in plant adaption to adverse environmental stresses, an idea that was also supported by other studies [61, 6466]. These identified PHD finger genes can then serve as a source of candidate genes for genetic engineering and improvement of Brassica crops against abiotic stresses.…”
Section: Discussionsupporting
confidence: 61%
“…In this study, a total of 145 PHD finger proteins containing 233 PHD domains were identified from the current version of the B. rapa proteome database (Additional file 2: Table S1). This number is considerably higher than those previously identified in maize (67) [64], poplar (73) [65] and rice (59) [66, 96], pear (31) [97] and moso bamboo (60) [67], although it might not yet be exhaustive as other PHD-suspected domain-containing proteins were also detected (Additional file 2: Table S2). This is the consequence of the WGT event occurred ~ 15.9 MYA in Brassica ancestor followed by gene losing [42, 47, 71], while only one tandem duplication event was observed among these PHD finger genes (Fig.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The most significant SNP marker, S1_13767032, was located on 0.497 kb upstream of the Oeu046142.1 gene. This gene is annotated as a PHD finger transcription factor and the family to which this gene belongs, plays a key role in regulating plant growth and development 86 . The analysis of transcriptomes provides genomic resources for functional annotation to discover genes for olive breeding 87 .…”
Section: Discussionmentioning
confidence: 99%
“…7d). In rice ( O. sativa ), five OsPHD genes were significantly induced while two inhibited by ABA [35]. In soybean, expression of GmPHD 1–6 were induced after ABA and drought treatment, and GmPHD2 transgene upregulated expression of ABA responsive bZIP transcription factor ABI5 [5].…”
Section: Discussionmentioning
confidence: 99%